ANALISIS KESALAHAN EJAAN DALAM SOAL-SOAL UJIAN SEMESTER SMP NEGERI 1 LANGSA - Tara Astika Bangun (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
The study, titled "Analysis of Spelling Errors in questions Semester Exam SMP Negeri 1 Langsa" This aims to describe the use of spelling mistakes in the semester exam questions SMP Negeri 1 Langsa and describe aspects of the dominant error occurred on such questions. The population was exam questions 2013/2014 semester of the school year about twelve. The population-based sample set of five questions, namely about Social Studies, Science, Indonesian, local content, and Religion. The samples done by purposive sampling technique. The method used is descriptive method. Data collected by the study of engineering documentation and data processing was done by using qualitative and quantitative analysis. The results of the analysis of data obtained as a whole amounted to 341 errors. EYD errors include capitalization amounts to 107 (31.38%), the use of italics totaled 15 (4.40%), use of bold numbered 3 (0.88%), the writing of said derivatives totaled 7 (2, 05%), writing the next word was 26 (7.62%), writing of the particles numbered 1 (0.29%), the writing stands totaling 4 (1.17%), the writing element uptake amounted to 20 (5.87%), punctuation usage totaled 142 (41.64%), the removal of spaces numbered 5 (1.47%), and excessive use of spaces totaling 11 (3.23%). Based on the number of such errors is the dominant use of punctuation errors.